Stainless steel foil, electrode and battery

CN122996217APending Publication Date: 2026-10-27NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580023495.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-03-26
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0026]本公开的不锈钢箔在涂布电极浆料时能够充分抑制电极浆料的缩孔。本公开的电极具备本公开的不锈钢箔。本公开的电池具备本公开的电极。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996217A_ABST
    Figure CN122996217A_ABST
Patent Text Reader

Abstract

Provided is a stainless steel foil capable of sufficiently suppressing shrinkage of electrode slurry when coating the electrode slurry. The stainless steel foil of the present disclosure has a foil main body composed of stainless steel, and the amount of organic residue on the surface of the foil main body is 2.0 mg / m 2 The following.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to stainless steel foil, electrodes using the stainless steel foil as current collectors, and batteries using the electrodes. Background Technology

[0002] To date, primary and secondary batteries have been used as power sources for various electronic devices. In recent years, with the widespread adoption of small electronic devices such as home video cameras, laptops, and smartphones, secondary batteries, represented by lithium-ion batteries, are rapidly gaining popularity.

[0003] A secondary battery comprises electrodes with positive and negative electrodes, and an electrolyte. In both the positive and negative electrodes, an electrode binder layer is formed on the current collector. The electrode binder layer is a layer containing active materials. The electrode binder layer of a lithium-ion battery, for example, consists of active materials capable of absorbing and releasing lithium ions during charging and discharging, conductive additives that help improve electronic conductivity, and an adhesive for bonding the active materials to each other or to the current collector. On the other hand, the current collector functions to supply current to the active materials and serves as a substrate for holding the electrode binder layer.

[0004] A method for forming an electrode paste layer on a current collector is described below. The electrode paste material is mixed and dispersed with a solvent to prepare a paste-like electrode slurry. The electrode slurry is then coated onto the surface of the current collector. Subsequently, the electrode paste is dried to form an electrode paste layer on the current collector.

[0005] Metal foil is used as a raw material for current collectors in secondary batteries. For example, in lithium-ion batteries, copper foil is used as the negative current collector and aluminum foil as the positive current collector. On the other hand, it is sometimes envisioned that secondary batteries will be used in even harsher environments than those previously discussed. Therefore, the raw materials for current collectors are required to have higher strength and better heat resistance than copper or aluminum foil. As a result, stainless steel foil, which has superior strength and heat resistance compared to copper and aluminum foil, is gradually gaining attention as a raw material for current collectors.

[0006] Japanese Patent Application Publication No. 2010-033782 (Patent Document 1) discloses a technique for applying stainless steel foil to current collectors.

[0007] The current collector for lithium-ion secondary batteries disclosed in Patent Document 1 is composed of a plate-like body of ferritic stainless steel. This ferritic stainless steel plate-like body, by mass%, contains Cr: 12-32%, C: less than 0.015%, Si: less than 0.5%, Mn: less than 2%, and optionally also contains one or more of Mo: less than 2%, Ni: less than 2%, and Cu: less than 2%, or also contains one or more of Nb: less than 0.8%, Ti: less than 0.4%, Al: less than 0.5%, and B: less than 0.3%, with the remainder consisting of Fe and unavoidable impurities. The current collector also has a roughened surface on at least one side, the roughened surface forming pitting depressions, the area of ​​the portion without pits being 40% or less (including 0%), and the surface roughness SPa measured by a scanning confocal laser microscope being 0.1 μm or more. In Patent Document 1, a roughened surface is formed by performing surface treatment on the stainless steel foil, thereby reducing the contact resistance between the stainless steel foil and the electrode adhesive layer, and thus improving the adhesion between the stainless steel foil and the electrode adhesive layer.

[0008] Prior art literature

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Application Publication No. 2010-033782 Summary of the Invention

[0011] The technical problem that the invention aims to solve

[0012] An oxide coating (also known as a passivation coating) is formed on the surface of ordinary stainless steel. As a result, stainless steel foil has high corrosion resistance. On the other hand, when stainless steel foil is used as a current collector, the resistance with the electrode flux layer increases due to the presence of the oxide coating. Therefore, for stainless steel foil used as a current collector, surface treatment as proposed in Patent Document 1 is mostly performed. However, performing such surface treatment leads to increased manufacturing costs or reduced productivity. Therefore, research has begun on using untreated stainless steel foil as a current collector by improving the active substances or conductive additives contained in the electrode flux layer. Here, untreated stainless steel foil refers to stainless steel foil that has been processed to a specified thickness through a general rolling process and has not undergone any surface treatment other than degreasing.

[0013] However, it has been found that the coatability of electrode paste is reduced in untreated stainless steel foil compared to surface-treated stainless steel foil (hereinafter referred to as surface-treated stainless steel foil). Specifically, it has been found that pinholes in the electrode paste occur in untreated stainless steel foil, sometimes resulting in uneven coating of the electrode paste. If the electrode paste cannot be coated evenly, it is already difficult to manufacture electrodes. Therefore, there is a need to develop stainless steel foil that can suppress pinholes in the electrode paste even without surface treatment.

[0014] The purpose of this disclosure is to provide a stainless steel foil capable of sufficiently suppressing pinholes in the electrode paste during coating, and to use the stainless steel foil as an electrode for a current collector and a battery using the electrode.

[0015] Technical means for solving technical problems

[0016] The stainless steel foil disclosed herein,

[0017] It has a foil body made of stainless steel.

[0018] The amount of organic residue on the surface of the foil body is 2.0 mg / m³. 2 the following.

[0019] The electrodes disclosed herein possess:

[0020] The stainless steel foil disclosed herein; and

[0021] An electrode mixture layer is formed on the surface of the stainless steel foil.

[0022] The battery disclosed herein has the following features:

[0023] The electrodes of this disclosure; and

[0024] Electrolytes.

[0025] Invention Effects

[0026] The stainless steel foil of this disclosure can effectively suppress pinholes in the electrode slurry during coating. The electrode of this disclosure incorporates the stainless steel foil of this disclosure. The battery of this disclosure incorporates the electrode of this disclosure. Attached Figure Description

[0027] Figure 1 This is a graph showing the relationship between the amount of organic residue on the surface of stainless steel foil and the area of ​​the pinholes when coating electrode paste. Detailed Implementation

[0028] The inventors have investigated a method for obtaining a stainless steel foil that can sufficiently suppress pinholes in the electrode paste during coating. As a result, the inventors have obtained the following insights.

[0029] In the typical manufacturing process of stainless steel foil, after processing into a specified thickness and surface shape through rolling and other processes, a degreasing treatment is performed. Lubricating oil and other organic residues used in the processing remain on the surface of the stainless steel foil substrate. If electrode paste is applied with these organic residues on the foil substrate surface, the ends of the coated portion will bend, or the edges of the coated portion will bulge. Such poor coating reduces the performance of the electrode. Therefore, a degreasing treatment is performed before applying the electrode paste to remove organic residues from the foil substrate surface. Organic solvents, acids, or alkalis are generally used to clean the stainless steel foil during the degreasing treatment. Previously, in surface-treated stainless steel foil used as a current collector, this degreasing treatment suppressed the aforementioned coating defects. Therefore, it is believed that by performing a degreasing treatment, organic residues on the foil substrate surface are sufficiently removed.

[0030] On the other hand, the inventors attempted to coat electrode paste onto stainless steel foil that had not undergone surface treatment, and the results showed that coating defects occurred as described above. Specifically, the electrode paste had low affinity with the foil substrate, resulting in pinholes in the electrode paste. The inventors conducted an in-depth study on the causes of pinholes in the electrode paste and concluded that even after degreasing, trace amounts of organic residue remained, which could potentially cause pinholes in the electrode paste.

[0031] The inventors actually measured the amount of organic residue on the surface of the foil body after degreasing treatment. Specifically, a stainless steel foil having a foil body having a chemical composition equivalent to SUS430LX as specified in JIS G 4305 (2015) was cold-rolled to a thickness of 10 μm. The rolled stainless steel foil was then subjected to organic solvent degreasing as a routine degreasing treatment. Specifically, the metal foil was immersed in a cleaning solvent bath for 30 seconds. Isohexane at room temperature was used as the cleaning solvent. After removing the stainless steel foil from the cleaning solvent bath, it was allowed to dry thoroughly to allow the cleaning solvent to evaporate. The amount of organic residue present on the surface of the foil body of the degreased stainless steel foil was determined by the following method.

[0032] [Methods for determining the amount of organic residue]

[0033] Twenty 0.06m pieces were collected from the main body of the stainless steel foil. 2 Test pieces of various sizes were collected. Sufficient amounts of chloroform were sprayed onto both sides of all collected test pieces to extract the organic matter adhering to the surface. Afterwards, all the chloroform used in the extraction was recovered. The recovered chloroform was completely evaporated using a rotary evaporator, and the mass (mg) of the residue was determined. The mass of the obtained residue was divided by the total surface area of ​​20 test pieces (2.40 m²). 2 The obtained value is used as the amount of organic residue (mg / m³) on the surface of the stainless steel foil body. 2 ).

[0034] The test results confirmed that 2.4 mg / m³ of residue remained on the surface of the degreased foil substrate. 2 Such trace amounts of organic residue. Therefore, the relationship between trace amounts of organic residue on the surface of the foil substrate and the coating properties of the electrode paste was further investigated. Specifically, stainless steel foils that had undergone degreasing treatment under various conditions were prepared. Furthermore, the chemical composition of the foil substrate was the same as that studied above, equivalent to SUS430LX as specified in JIS G 4305 (2015). The thickness of the foil substrate was 10 μm. Based on the method described above in [Method for Determination of Organic Residue Amount], the amount of organic residue on the surface of the foil substrate of each stainless steel foil after degreasing treatment was determined. Then, the coating properties of the electrode paste in each stainless steel foil were evaluated by the following method.

[0035] [Evaluation Method for Electrode Slurry Coating Properties]

[0036] A test piece measuring 210 mm in length and 150 mm in width was collected from the stainless steel foil substrate. Next, an electrode paste was prepared. Specifically, Si powder, acetylene black (AB), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were mixed and kneaded at a mass ratio of 95:1:1:2. Water was used as the solvent, resulting in a solid content of 41% by mass. The prepared electrode paste was then applied to the test piece using a coater with a coating width of 80 mm and a gap of 50 μm. For uniform coating, the length of the coated portion was 150 mm, and the center of the coating portion in the width direction was aligned with the center of the test piece in the width direction. The coated test piece was then heated at 75°C for 20 minutes to dry the electrode paste. Using the dried test piece, the area of ​​the craters in the electrode paste was determined. Specifically, within the coating section, excluding the area extending 20 mm along the length from the coating start position and the area extending 5 mm along the length from the coating end position (length 125 mm × width 80 mm), the area (mm²) of the uncoated electrode paste is calculated using known image processing techniques. 2 The obtained value is taken as the area (mm²) of the shrinkage cavity in the test piece. 2 The area (mm²) of the shrinkage cavity in the three test pieces. 2 The arithmetic mean of the values ​​is taken as the area (mm²) of the shrinkage cavity of the stainless steel foil. 2 ).

[0037] The area (mm²) of the shrinkage cavity of each stainless steel foil obtained in this way 2 The curve obtained by plotting the amount of organic residue on the surface of the stainless steel foil body is shown in the figure below. Figure 1 . Reference Figure 1 If the amount of organic residue on the surface of the foil body is 2.0 mg / m 2Below this, the area of ​​the shrinkage cavity is significantly reduced, becoming 0m. 2 In this case, no pinholes in the electrode paste during coating will occur. That is, it was determined that by reducing the amount of organic residue on the surface of the foil substrate to 2.0 mg / m³... 2 The following methods can significantly suppress shrinkage cavities in electrode pastes.

[0038] The stainless steel foil, the electrode, and the battery of this embodiment are completed based on the above technical concept and have the following structure.

[0039] The first component is stainless steel foil.

[0040] It has a foil body made of stainless steel.

[0041] The amount of organic residue on the surface of the foil body is 2.0 mg / m³. 2 the following.

[0042] The second component is stainless steel foil.

[0043] It is the first component of stainless steel foil.

[0044] The three-dimensional arithmetic mean roughness Sa of the surface of the foil body is less than 0.15 μm.

[0045] The third component is stainless steel foil.

[0046] It is a stainless steel foil composed of the first or second structure.

[0047] The stainless steel mentioned is a ferritic stainless steel.

[0048] The chemical composition of the foil body is as follows: by mass%, it contains...

[0049] C: 0.001~0.030%

[0050] Si: 0.01~1.00%

[0051] Mn: 0.01~1.00%,

[0052] P: 0.001~0.050%,

[0053] S: 0.001~0.030%

[0054] Ni: 0.01~0.50%

[0055] Cr: 12.00~20.00%

[0056] Mo: 0.01~2.50%,

[0057] N: 0~0.100%

[0058] Ti: 0~0.80%,

[0059] Nb: 0~0.80%, and

[0060] Zr: 0~0.80%,

[0061] The remainder consists of Fe and impurities.

[0062] The fourth component is stainless steel foil.

[0063] It is a stainless steel foil composed of the first or second structure.

[0064] The stainless steel mentioned is an austenitic stainless steel.

[0065] The chemical composition of the foil body is as follows: by mass%, it contains...

[0066] C: 0.001~0.150%

[0067] Si: 0.01~1.00%

[0068] Mn: 0.01~2.00%

[0069] P: 0.001~0.045%,

[0070] S: 0.001~0.030%

[0071] Ni: 6.00~15.00%

[0072] Cr: 16.00~20.00%

[0073] Mo: 0 ~ 2.50%,

[0074] N: 0~0.100%

[0075] Ti: 0~0.50%,

[0076] Nb: 0~0.12%, and

[0077] Zr: 0~0.10%,

[0078] The remainder consists of Fe and impurities.

[0079] The first electrode configuration includes:

[0080] Stainless steel foil of any one of the first to fourth compositions; and

[0081] An electrode mixture layer is formed on the surface of the stainless steel foil.

[0082] The first type of battery has the following features:

[0083] The first type of electrode; and

[0084] Electrolytes.

[0085] The stainless steel foil, the electrode, and the battery of this embodiment will be described in detail below. Furthermore, unless otherwise specified, the percentage of elements (%) refers to mass percentage.

[0086] [Stainless Steel Foil]

[0087] The stainless steel foil of this embodiment includes a foil body made of stainless steel. That is, the stainless steel foil of this embodiment may also consist only of a foil body made of stainless steel.

[0088] Stainless steel can be either ferritic or austenitic. Ferritic stainless steel refers to steel with a chromium content of 10.5% or more and a microstructure primarily composed of ferrite. Austenitic stainless steel refers to steel with a chromium content of 10.5% or more and a microstructure primarily composed of austenite. Furthermore, in this specification, stainless steel foil whose main body is composed of ferritic stainless steel will also be referred to as "ferritic stainless steel foil." In this specification, stainless steel foil whose main body is composed of austenitic stainless steel will also be referred to as "austenitic stainless steel foil."

[0089] [Amount of organic residue on the surface]

[0090] In the stainless steel foil of this embodiment, the amount of organic residue on the surface of the foil body is 2.0 mg / m³. 2 the following.

[0091] Here, organic residue on the surface of the foil body refers to residue composed mainly of organic compounds, primarily the lubricating oil used in the rolling process. The amount of organic residue on the surface of the foil body can be determined using the method described in the above-mentioned [Method for Determining the Amount of Organic Residue].

[0092] If the amount of organic residue on the surface exceeds 2.0 mg / m³ 2 If the electrode paste is applied without surface treatment, pinholes will occur. Even a small number of pinholes will significantly reduce the electrode's performance.

[0093] like Figure 1 As shown, if the amount of organic residue on the surface is 2.0 mg / m³ 2 The coating properties of the electrode paste are significantly improved. Therefore, even when coating the electrode paste without surface treatment, pinholes in the electrode paste can be effectively suppressed.

[0094] Therefore, the amount of organic residue on the surface of the foil substrate was set to 2.0 mg / m². 2 the following.

[0095] There is no specific lower limit for the amount of organic residue on the surface. However, considering typical industrial production, the lower limit for organic residue on the surface is, for example, 0.1 mg / m³. 2 .

[0096] The preferred upper limit for the amount of organic residue on the surface is 1.9 mg / m³. 2 A further preferred value is 1.7 mg / m³. 2 A further preferred value is 1.5 mg / m³. 2 .

[0097] [Chemical Composition]

[0098] In the stainless steel foil of this embodiment, the chemical composition of the foil body can be composed of the chemical composition of a known ferritic stainless steel or a known austenitic stainless steel.

[0099] In the case where the stainless steel foil in this embodiment is a ferritic stainless steel foil, the chemical composition of the foil body may, for example, satisfy any one of the groups consisting of SUS405, SUS410L, SUS429, SUS430, SUS430LX, SUS430J1L, SUS434, SUS436L, SUS436J1L, SUS443J1, SUS444, SUS445J1, SUS445J2, SUS447J1 and SUSXM27 as specified in JIS G 4305 (2015).

[0100] In the case that the stainless steel foil in this embodiment is a ferritic stainless steel foil, the chemical composition of the foil body may, for example, satisfy any one of the following groups as specified in ASTM A 240 (2006): 403, 405, 409L, 410, 410L, 410S, 415, 420J1, 420J2, 420, 429, 429J1, 430, 430J1L, 430LX, 430Ti, 434, 436, 436J1L, 439, 441, 444, 445, 445J1, 445J2, 446, 447, and 448.

[0101] In the case where the stainless steel foil in this embodiment is a ferritic stainless steel foil, the chemical composition of the foil body may contain, for example, the following elements.

[0102] C: 0.001~0.030%

[0103] Carbon (C) increases the strength of ferritic stainless steel foil. This effect is fully achieved when the C content is 0.001% or higher.

[0104] On the other hand, if the C content is below 0.030%, the formation of a Cr-deficient layer caused by the formation of Cr carbides can be suppressed. As a result, the embrittlement of the oxide coating is suppressed, and the corrosion resistance of the ferritic stainless steel foil is improved.

[0105] Therefore, the preferred C content is 0.001~0.030%.

[0106] The lower limit for the C content is 0.003%, and the lower limit is 0.005%.

[0107] The upper limit for the C content is further preferably 0.025%, and even more preferably 0.020%.

[0108] Si: 0.01~1.00%

[0109] Silicon (Si) is used to deoxidize steel during the steelmaking process. The desired effect can be achieved when the Si content is 0.01% or higher.

[0110] On the other hand, if the Si content is below 1.00%, the processability of ferritic stainless steel foil is improved.

[0111] Therefore, the preferred Si content is 0.01~1.00%.

[0112] The lower limit for the Si content is 0.03%, and the lower limit is 0.05%.

[0113] The upper limit for the Si content is further preferably 0.90%, and more preferably 0.80%.

[0114] Mn: 0.01~1.00%

[0115] Manganese (Mn) improves the strength of ferritic stainless steel foil. The above effect can be fully achieved if the Mn content is 0.01% or higher.

[0116] On the other hand, if the Mn content is below 1.00%, the corrosion resistance of ferritic stainless steel foil is improved.

[0117] Therefore, the preferred Mn content is 0.01~1.00%.

[0118] The lower limit for the Mn content is 0.03%, and the lower limit is 0.05%.

[0119] The upper limit for the Mn content is further preferred to be 0.90%, and even more preferred to be 0.80%.

[0120] P: 0.001~0.050%

[0121] Phosphorus (P) is an impurity. It typically contains more than 0.001% P.

[0122] On the other hand, if the P content is below 0.050%, the processability and corrosion resistance of ferritic stainless steel foil are improved.

[0123] Therefore, the preferred P content is 0.001~0.050%.

[0124] The phosphorus (P) content is preferably as low as possible. However, excessively reducing the P content increases manufacturing costs. Therefore, considering typical industrial production, the preferred lower limit for the P content is 0.002%, more preferably 0.010%.

[0125] The upper limit for the P content is further preferred to be 0.045%, and even more preferred to be 0.040%.

[0126] S: 0.001~0.030%

[0127] Sulfur (S) is an impurity. It usually contains more than 0.001% S.

[0128] On the other hand, if the sulfur content is below 0.030%, the processability and corrosion resistance of ferritic stainless steel foil are improved.

[0129] Therefore, the preferred S content is 0.001~0.030%.

[0130] The sulfur content is preferably as low as possible. However, excessively reducing the sulfur content increases manufacturing costs. Therefore, considering typical industrial production, the preferred lower limit for the sulfur content is 0.002%, more preferably 0.010%.

[0131] The upper limit for the S content is further preferably 0.025%, and even more preferably 0.020%.

[0132] Ni: 0.01~0.50%

[0133] Nickel (Ni) improves the corrosion resistance of ferritic stainless steel foil. This effect is fully achieved when the Ni content is 0.01% or higher.

[0134] On the other hand, if the Ni content is below 0.50%, the processability of ferritic stainless steel foil is improved.

[0135] Therefore, the preferred Ni content is 0.01~0.50%.

[0136] The lower limit for the Ni content is 0.03%, and the lower limit is 0.05%.

[0137] The upper limit for the Ni content is further preferably 0.40%, and more preferably 0.30%.

[0138] Cr: 12.00~20.00%

[0139] Chromium (Cr) forms an oxide coating, improving the corrosion resistance of ferritic stainless steel foil. This effect is fully achieved when the Cr content is 12.00% or higher.

[0140] On the other hand, if the Cr content is below 20.00%, the processability of ferritic stainless steel foil is improved.

[0141] Therefore, the preferred Cr content is 12.00~20.00%.

[0142] The lower limit for the Cr content is 12.50%, and the higher limit is 13.00%.

[0143] The upper limit for the Cr content is further preferred to be 19.00%, and further preferred to be 18.00%.

[0144] Mo: 0.01~2.50%

[0145] Molybdenum (Mo) improves the strength and corrosion resistance of ferritic stainless steel foil. These effects are fully achieved when the Mo content is 0.01% or higher.

[0146] On the other hand, if the Mo content is below 2.50%, the processability of ferritic stainless steel foil is improved.

[0147] Therefore, the preferred Mo content is 0.01~2.50%.

[0148] The lower limit for the Mo content is 0.03%, and the lower limit is 0.05%.

[0149] The upper limit for the Mo content is further preferred to be 2.40%, and even more preferred to be 2.30%.

[0150] N: 0~0.100%

[0151] It can also be nitrogen-free (N). That is, the N content can be 0%.

[0152] On the other hand, if the content of N is less than 0.100%, the strength of the ferritic stainless steel foil is improved.

[0153] Therefore, the preferred N content is 0~0.100%.

[0154] The lower limit for the N content is more than 0%, more preferably 0.001%, and more preferably 0.003%.

[0155] The upper limit for the N content is further preferred to be 0.090%, and further preferred to be 0.080%.

[0156] Ti: 0~0.80%

[0157] It can also be free of titanium (Ti). That is, the Ti content can be 0%.

[0158] On the other hand, if the Ti content is below 0.80%, C is fixed, inhibiting the formation of Cr carbides. Therefore, the formation of the Cr-deficient layer is suppressed. As a result, the embrittlement of the oxide coating is suppressed, and the corrosion resistance of the ferritic stainless steel foil is improved.

[0159] Therefore, the preferred Ti content is 0~0.80%.

[0160] The further preferred lower limit for the Ti content is more than 0%, more preferably 0.01%, and more preferably 0.03%.

[0161] The upper limit for the Ti content is further preferred to be 0.70%, and further preferred to be 0.60%.

[0162] Nb: 0~0.80%

[0163] It can also be free of niobium (Nb). That is, the Nb content can be 0%.

[0164] On the other hand, if the Nb content is less than 0.80%, the corrosion resistance of the ferritic stainless steel foil is improved.

[0165] Therefore, the preferred Nb content is 0~0.80%.

[0166] The further preferred lower limit for Nb content is more than 0%, more preferably 0.01%, and more preferably 0.03%.

[0167] The upper limit for Nb content is further preferred to be 0.70%, and even more preferred to be 0.60%.

[0168] Zr: 0~0.80%

[0169] It can also be free of zirconium (Zr). That is, the Zr content can be 0%.

[0170] On the other hand, if the Zr content is less than 0.80%, the corrosion resistance of ferritic stainless steel foil is improved.

[0171] Therefore, the preferred Zr content is 0~0.80%.

[0172] The further preferred lower limit for Zr content is more than 0%, more preferably 0.01%, and more preferably 0.03%.

[0173] The upper limit for Zr content is further preferred to be 0.70%, and further preferred to be 0.60%.

[0174] In the case of a ferritic stainless steel foil in this embodiment, the remaining portion of the preferred chemical composition of the foil body consists of Fe and impurities. Here, impurities in the chemical composition refer to substances that may be introduced from raw materials or the manufacturing environment during the industrial manufacture of ferritic stainless steel foil, and are substances that are permissible within a range that do not adversely affect the ferritic stainless steel foil of this embodiment.

[0175] On the other hand, when the stainless steel foil in this embodiment is an austenitic stainless steel foil, the chemical composition of the foil body can, for example, satisfy the requirements of SUS301, SUS301L, SUS301J1, SUS302B, SUS304, SUS304Cu, SUS304L, SUS304N1, SUS304N2, SUS304LN, SUS304J1, SUS304J2, SUS305, SUS309S, SUS310S, SUS312L, SUS315J1, and SUS315J2 as specified in JIS G 4305 (2015). Choose any one of the following: SUS316, SUS316L, SUS316N, SUS316LN, SUS316Ti, SUS316J1, SUS316J1L, SUS317, SUS317L, SUS317LN, SUS317J1, SUS317J2, SUS836L, SUS890L, SUS321, SUS347, SUSXM7, and SUSXM15J1.

[0176] In the case where the stainless steel foil in this embodiment is an austenitic stainless steel foil, the chemical composition of the foil body may contain, for example, the following elements.

[0177] C: 0.001~0.150%

[0178] Carbon (C) increases the strength of austenitic stainless steel foil. This effect is fully achieved when the C content is 0.001% or higher.

[0179] On the other hand, if the C content is below 0.150%, the formation of a Cr-deficient layer caused by the formation of Cr carbides can be suppressed. As a result, the embrittlement of the oxide coating is suppressed, and the corrosion resistance of the austenitic stainless steel foil is improved.

[0180] Therefore, the preferred C content is 0.001~0.150%.

[0181] The lower limit for the C content is 0.003%, and the lower limit is 0.005%.

[0182] The upper limit for the C content is further preferred to be 0.130%, and further preferred to be 0.100%.

[0183] Si: 0.01~1.00%

[0184] Silicon (Si) is used to deoxidize steel during the steelmaking process. The desired effect can be achieved when the Si content is 0.01% or higher.

[0185] On the other hand, if the Si content is below 1.00%, the processability of austenitic stainless steel foil is improved.

[0186] Therefore, the preferred Si content is 0.01~1.00%.

[0187] The lower limit for the Si content is 0.03%, and the lower limit is 0.05%.

[0188] The upper limit for the Si content is further preferably 0.90%, and more preferably 0.80%.

[0189] Mn: 0.01~2.00%

[0190] Manganese (Mn) increases the strength of austenitic stainless steel foil. Mn also stabilizes austenite. These effects are fully achieved when the Mn content is 0.01% or higher.

[0191] On the other hand, if the Mn content is below 2.00%, the corrosion resistance of austenitic stainless steel foil is improved.

[0192] Therefore, the preferred Mn content is 0.01~2.00%.

[0193] The lower limit for the Mn content is 0.03%, and the lower limit is 0.05%.

[0194] The upper limit for the Mn content is further preferred to be 1.80%, and even more preferred to be 1.60%.

[0195] P: 0.001~0.045%

[0196] Phosphorus (P) is an impurity. It typically contains more than 0.001% P.

[0197] On the other hand, if the P content is below 0.045%, the processability and corrosion resistance of austenitic stainless steel foil are improved.

[0198] Therefore, the preferred P content is 0.001~0.045%.

[0199] The phosphorus (P) content is preferably as low as possible. However, excessively reducing the P content increases manufacturing costs. Therefore, considering typical industrial production, the preferred lower limit for the P content is 0.002%, more preferably 0.010%.

[0200] The upper limit for the P content is further preferred to be 0.040%, and further preferred to be 0.030%.

[0201] S: 0.001~0.030%

[0202] Sulfur (S) is an impurity. It usually contains more than 0.001% S.

[0203] On the other hand, if the sulfur content is below 0.030%, the processability and corrosion resistance of austenitic stainless steel foil are improved.

[0204] Therefore, the preferred S content is 0.001~0.030%.

[0205] The sulfur content is preferably as low as possible. However, excessively reducing the sulfur content increases manufacturing costs. Therefore, considering typical industrial production, the preferred lower limit for the sulfur content is 0.002%, more preferably 0.010%.

[0206] The upper limit for the S content is further preferably 0.025%, and even more preferably 0.020%.

[0207] Ni: 6.00~15.00%

[0208] Nickel (Ni) stabilizes austenite. Ni also improves the ductility of austenitic stainless steel foil. These effects are fully achieved when the Ni content is 6.00% or higher.

[0209] On the other hand, if the Ni content is below 15.00%, the processability of austenitic stainless steel foil is improved.

[0210] Therefore, the preferred Ni content is 6.00~15.00%.

[0211] The lower limit for the Ni content is 6.20%, and the lower limit is 6.50%.

[0212] The upper limit for the Ni content is further preferred to be 14.00%, and even more preferred to be 13.00%.

[0213] Cr: 16.00~20.00%

[0214] Chromium (Cr) forms an oxide coating, improving the corrosion resistance of austenitic stainless steel foil. This effect is fully achieved when the Cr content is 16.00% or higher.

[0215] On the other hand, if the Cr content is below 20.00%, the processability of austenitic stainless steel foil is improved.

[0216] Therefore, the preferred Cr content is 16.00~20.00%.

[0217] The lower limit for the Cr content is 16.50%, and the higher limit is 17.00%.

[0218] The upper limit for the Cr content is further preferred to be 19.50%, and further preferred to be 19.00%.

[0219] Mo: 0 ~ 2.50%

[0220] It can also be free of molybdenum (Mo). That is, the Mo content can be 0%.

[0221] On the other hand, if the Mo content is below 2.50%, the strength and corrosion resistance of austenitic stainless steel foil are improved.

[0222] Therefore, the preferred Mo content is 0~2.50%.

[0223] The further preferred lower limit for the Mo content is more than 0%, more preferably 0.01%, more preferably 0.03%, and more preferably 0.05%.

[0224] The upper limit for the Mo content is further preferred to be 2.40%, and even more preferred to be 2.30%.

[0225] N: 0~0.100%

[0226] It can also be nitrogen-free (N). That is, the N content can be 0%.

[0227] On the other hand, if the nitrogen content is less than 0.100%, the strength of the austenitic stainless steel foil is improved.

[0228] Therefore, the preferred N content is 0~0.100%.

[0229] The lower limit for the N content is more than 0%, more preferably 0.001%, and more preferably 0.003%.

[0230] The upper limit for the N content is further preferred to be 0.090%, and further preferred to be 0.080%.

[0231] Ti: 0~0.50%

[0232] It can also be free of titanium (Ti). That is, the Ti content can be 0%.

[0233] On the other hand, if the Ti content is less than 0.50%, the C content is fixed, inhibiting the formation of Cr carbides. Therefore, the formation of the Cr-deficient layer is suppressed. As a result, the embrittlement of the oxide coating is inhibited, and the corrosion resistance of the austenitic stainless steel foil is improved.

[0234] Therefore, the preferred Ti content is 0~0.50%.

[0235] The further preferred lower limit for the Ti content is more than 0%, more preferably 0.01%, and more preferably 0.03%.

[0236] The upper limit for the Ti content is further preferably 0.40%, and more preferably 0.30%.

[0237] Nb: 0~0.12%

[0238] It can also be free of niobium (Nb). That is, the Nb content can be 0%.

[0239] On the other hand, if the Nb content is less than 0.12%, the corrosion resistance of austenitic stainless steel foil is improved.

[0240] Therefore, the preferred Nb content is 0~0.12%.

[0241] The further preferred lower limit for Nb content is more than 0%, more preferably 0.01%, and more preferably 0.03%.

[0242] The upper limit for Nb content is further preferred to be 0.70%, and even more preferred to be 0.60%.

[0243] Zr: 0~0.10%

[0244] It can also be free of zirconium (Zr). That is, the Zr content can be 0%.

[0245] On the other hand, if the content of Zr is less than 0.10%, the corrosion resistance of austenitic stainless steel foil is improved.

[0246] Therefore, the preferred Zr content is 0~0.10%.

[0247] The further preferred lower limit for Zr content is more than 0%, more preferably 0.01%, and more preferably 0.03%.

[0248] The upper limit for Zr content is further preferred to be 0.09%, and further preferred to be 0.08%.

[0249] In the case of an austenitic stainless steel foil in this embodiment, the remaining portion of the preferred chemical composition of the foil body consists of Fe and impurities. Here, impurities in the chemical composition refer to substances that may be introduced from raw materials or the manufacturing environment during the industrial manufacture of austenitic stainless steel foil, and are substances that are permissible within a range that do not adversely affect the austenitic stainless steel foil of this embodiment.

[0250] [Plate thickness]

[0251] In the stainless steel foil of this embodiment, the thickness of the foil body is not limited. The thickness of the foil body is, for example, 5 to 20 μm.

[0252] [The three-dimensional arithmetic mean roughness Sa of the surface]

[0253] Preferably, in the stainless steel foil of this embodiment, the three-dimensional arithmetic mean roughness Sa of the surface of the foil body is less than 0.15 μm.

[0254] In metal foils used as current collectors, a surface with a certain degree of unevenness is generally preferred over a completely smooth surface in order to improve adhesion to the electrode binder layer. However, in the stainless steel foil of this embodiment, the smoother the surface of the foil body, the better it can mitigate the organic residue content on the surface reaching 2.0 mg / m³. 2 The following degreasing conditions apply. Therefore, a smaller three-dimensional arithmetic mean roughness Sa of the foil body surface is preferred.

[0255] If the three-dimensional arithmetic mean roughness Sa is less than 0.15 μm, then by satisfying formula (B2) described later in the degreasing process of the stainless steel foil manufacturing process of this embodiment, the amount of organic residue on the surface can be reduced to 2.0 mg / m². 2 In other words, compared to cases where the three-dimensional arithmetic mean roughness Sa is above 0.15 μm, stainless steel foil with a surface three-dimensional arithmetic mean roughness Sa less than 0.15 μm can achieve a surface organic residue level of 2.0 mg / m² in a shorter time and at a lower cost. 2 the following.

[0256] There is no particular limitation on the lower limit of the three-dimensional arithmetic mean roughness Sa. As mentioned above, a smaller three-dimensional arithmetic mean roughness Sa is preferred. However, considering typical industrial production, the lower limit of the three-dimensional arithmetic mean roughness Sa is, for example, 0.02 μm.

[0257] The upper limit for the three-dimensional arithmetic mean roughness Sa is 0.14 μm, and the upper limit for the three-dimensional arithmetic mean roughness is 0.12 μm.

[0258] [Method for determining the three-dimensional arithmetic mean surface roughness Sa]

[0259] The three-dimensional arithmetic mean roughness Sa of the foil body surface is obtained by the following method.

[0260] Test pieces were collected from the main body of stainless steel foil. The size of the test pieces was not particularly limited. One surface of the test piece was used as the measurement surface. The surface shape of the measurement surface was measured using a laser microscope. For example, a Keyence VK-X100 laser microscope was used. The magnification was set to 2000x, and a measurement area of ​​280µm × 200µm was measured. Specifically, to measure the entire area within the measurement region, four locations within the region were measured with a field of view of 145µm × 109µm, obtaining surface images. The four surface images were stitched together using the accompanying image stitching software to obtain a surface image of the 280µm × 200µm measurement area. From the surface shape profile obtained by analyzing the surface image of the measurement area, a reference plane was established by cutting off 0.3% of the area from the side with lower brightness, generating a three-dimensional image. At this point, a high-pass filter with a cutoff wavelength of 50µm was used for filtering. A Gaussian filter was used for the filtering process. Within a 200μm × 150μm region of the obtained 3D image, the unfolded area ratio Sdr specified in ISO 25178-2:2012 is determined. The obtained value is taken as the 3D arithmetic mean roughness Sa (μm) of the surface of the stainless steel foil body.

[0261] [Application of the stainless steel foil in this embodiment]

[0262] The stainless steel foil of this embodiment exhibits excellent coating properties for the electrode paste. In particular, the stainless steel foil of this embodiment can suppress pinholes in the electrode paste even when used as a current collector without surface treatment. Therefore, it is suitable for use as a current collector in secondary batteries, such as lithium-ion batteries.

[0263] [Method for manufacturing stainless steel foil according to this embodiment]

[0264] This section describes an example of a method for manufacturing the stainless steel foil according to this embodiment. The method described below is an example for manufacturing the stainless steel foil of this embodiment. Therefore, the stainless steel foil having the above-described structure can also be manufactured by other manufacturing methods besides the method described below. However, the manufacturing method described below is a preferred example of the method for manufacturing the stainless steel foil of this embodiment.

[0265] An example of the method for manufacturing stainless steel foil according to this embodiment includes the following steps.

[0266] (Process 1) Raw material preparation process

[0267] (Process 2) Final cold rolling process

[0268] (Step 3) Degreasing process

[0269] The following is a description of each process.

[0270] [(Process 1) Raw Material Preparation Process]

[0271] In the raw material preparation process, stainless steel sheets with a thickness of tens to hundreds of µm are prepared as raw materials for manufacturing the stainless steel foil of this embodiment. For example, the raw material is a cold-rolled coil after hot-rolled coil has been cold-rolled. The raw material can be prepared through manufacturing or by purchasing it from a third party. That is, the process for preparing the raw material is not particularly limited.

[0272] In the case of manufacturing raw materials, they can be manufactured, for example, by the following methods: Molten steel with a desired chemical composition is produced. A slab is manufactured using the molten steel through continuous casting. The manufactured slab is then hot-worked and cold-rolled to produce a steel plate with a thickness of tens to hundreds of µm. The hot-working method is not particularly limited; any known method may be used. Hot-working, for example, is hot rolling. In the case of manufacturing raw materials by hot rolling, it is possible, for example, to manufacture them by the following methods.

[0273] After heating the manufactured slab, rough rolling and finish rolling are performed. At this time, the hot rolling conditions are not particularly limited; any known conditions can be appropriately set. The hot-rolled raw material can also be repeatedly subjected to cold rolling and annealing treatments as needed. The hot-rolled raw material can also undergo surface finishing rolling as needed. The hot-rolled and / or cold-rolled raw material is further subjected to annealing treatment. Through the above processes, the raw material for the stainless steel foil of this embodiment is prepared.

[0274] (Process 2) Final cold rolling process

[0275] In the final cold rolling process, the raw materials prepared in the raw material preparation process are cold rolled to obtain a stainless steel foil with a foil body having a specified thickness. In this embodiment, cold rolling can be carried out using known equipment, without particular limitation. For example, cold rolling can be carried out using a continuous rolling mill with multiple rolling stands arranged in a row, or it can be carried out using a reversible rolling mill.

[0276] In the final cold rolling process, the following conditions are preferably met.

[0277] (Preferred Condition 1) The arithmetic mean surface roughness Ra (μm) of the rolls used in the final cold rolling process and the rolling speed v (m / s) in the final cold rolling process satisfy Equation (A).

[0278] Ra×(1+log 10 v)≦ 0.28 (A).

[0279] [Regarding the preferred condition 1]

[0280] Defined as FA = Ra × (1 + log 10 v). FA is an index used to adjust the surface roughness of stainless steel foil in the final cold rolling process. The surface of the rolls used in the final cold rolling process is transferred onto the surface of the stainless steel foil body manufactured by this method. Therefore, the smaller the arithmetic mean roughness Ra (μm) of the surface of the rolls used in the final cold rolling process, the smaller the three-dimensional arithmetic mean roughness Sa of the surface of the manufactured stainless steel foil body. Furthermore, Ra includes the maximum value of the arithmetic mean roughness Ra of the surfaces of all rolls in contact with the foil body in the final cold rolling process (the arithmetic mean roughness Ra of the roll with the largest surface roughness). Additionally, in the final cold rolling process, if the rolling speed v (m / s) is high, the load on the foil body increases, making it easier for surface defects to occur. Furthermore, the amount of lubricating oil wound into the underside of the rolls increases, making it easier for pits (oil pits) to form on the surface of the foil body. Therefore, the slower the rolling speed v (m / s), the smaller the three-dimensional arithmetic mean roughness Sa of the surface of the manufactured stainless steel foil body.

[0281] If FA is below 0.28, the three-dimensional arithmetic mean roughness Sa of the foil body surface is less than 0.15 μm. Therefore, it is preferable to satisfy formula (A) in the final cold rolling process.

[0282] There is no specific lower limit for FA; if we consider typical industrial production, for example, it is 0.01.

[0283] [(Process 3) Degreasing process]

[0284] In the degreasing process, the stainless steel foil obtained in the final cold rolling process is degreased to remove surface organic residues. After degreasing, the stainless steel foil is rinsed with pure water. Then, the stainless steel foil is allowed to dry thoroughly.

[0285] The degreasing process must meet the following conditions.

[0286] (Condition 1) Degreasing is performed by PR electrolysis, with a polarity switching time t. s It takes more than 2 seconds.

[0287] (Condition 2) The concentration of the alkaline cleaning solution used in the degreasing process is defined as c (mol / L), and the degreasing time is defined as t. t (seconds), current density is defined as d (A / dm). 2When the surface roughness of the foil body is greater than or equal to 0.15 μm, equation (B1) is satisfied; when the surface roughness of the foil body is less than or equal to 0.15 μm, equation (B2) is satisfied.

[0288] c×log 10 t t ×d≧25.0 (B1)

[0289] c×log 10 t t ×d≧1.0 (B2).

[0290] [Regarding condition 1]

[0291] PR (Periodic Reversal) electrolytic degreasing is one method of electrolytic degreasing using an alkaline cleaning solution. It involves alternately switching the polarity (cathode or anode) of the stainless steel foil used as the electrode. The time required to switch the polarity of the stainless steel foil from cathode to anode or from anode to cathode is constant and is referred to as the polarity switching time t. s (seconds). Compared with other alkaline electrolytic degreasing methods, PR electrolytic degreasing has higher performance in removing organic residues.

[0292] In the degreasing process, if the polarity switching time t is implemented... s If the PR electrolytic degreasing is set to a duration of 2 seconds or more, then, assuming condition 2 is met, the amount of organic residue on the surface of the foil body becomes 2.0 mg / m². 2 the following.

[0293] Polarity switching time t s There is no specific upper limit, but if we consider typical industrial production, for example, 10 seconds.

[0294] [Regarding condition 2]

[0295] Defined as FB = c × log 10 t t ×d.

[0296] In addition, the defatting time t t (seconds) is the time it takes for the current to flow through the stainless steel foil. If the degreasing process satisfies condition 1 and FB satisfies formula (B1), then the amount of organic residue on the surface of the foil body becomes 2.0 mg / m³. 2The smoother the surface of the foil body, the easier it is to remove organic residues during the degreasing process. If the three-dimensional arithmetic mean roughness Sa of the foil body surface is less than 0.15 μm, then the foil body surface is sufficiently smooth. In this case, if the degreasing process satisfies condition 1 and FB satisfies equation (B2), then the amount of organic residue on the foil body surface becomes 2.0 mg / m³. 2 In other words, if the three-dimensional arithmetic mean roughness Sa of the foil substrate surface is less than 0.15 μm, then FB can also be greater than 1.0 and less than 25.0. Therefore, compared to the case where the three-dimensional arithmetic mean roughness Sa of the foil substrate surface is greater than 0.15 μm, even if the concentration c (mol / L) of the alkaline cleaning solution is low and the degreasing treatment time t is low, the FB can still achieve a certain result. t (seconds) short, current density d (A / dm) 2 The amount of organic residue on the surface of the foil body is small, and it is 2.0 mg / m³. 2 the following.

[0297] There is no specific limit to the upper limit of FB, but if we consider typical industrial production, it can be set at 100.0.

[0298] The stainless steel foil of this embodiment is manufactured using the above manufacturing method. The manufacturing method of the stainless steel foil of this embodiment may also include processes other than those described above. For example, a heat treatment process may be performed on the stainless steel foil after the degreasing process. In the heat treatment process, the stainless steel foil after the degreasing process is heated and held at a predetermined temperature. This removes residual stress accumulated in the stainless steel foil or imparts ductility. The heat treatment temperature is, for example, 300~1000°C.

[0299] [electrode]

[0300] The electrode of this embodiment includes the stainless steel foil of this embodiment and an electrode flux layer formed on the surface of the stainless steel foil. That is, in the electrode of this embodiment, the stainless steel foil of this embodiment is used as the current collector. The electrode of this embodiment can be either a positive or negative electrode. In other words, as long as the stainless steel foil and electrode flux layer of this embodiment are included, the structure of the electrode of this embodiment is not particularly limited.

[0301] [Electrode Mixture Layer]

[0302] In the electrode of this embodiment, the electrode binder layer is not particularly limited and can have a known structure. The electrode binder layer contains an active material. Furthermore, the electrode binder layer may also contain substances other than the active material. For example, the electrode binder layer may also contain a binder and a conductive additive. Additionally, the electrode binder layer for all-solid-state batteries may, for example, contain a solid electrolyte.

[0303] [Active Substances]

[0304] In the electrode of this embodiment, the active material contained in the electrode mixture layer is not particularly limited, and known active materials can be used. When the electrode is a positive electrode, the positive electrode active material can, for example, be derived from LiCoO2, LiNi... 1 / 3 Co 1 / 3 Mn 1 / 3 The active material can be any one or more of the following groups: ternary materials represented by O2, olivine materials represented by LiFePO4, and sulfur-based materials represented by S, Fe2S, Mo3S4, and sulfur-modified polyacrylonitrile. When the electrode is a negative electrode, the active material can also be, for example, carbon-based materials represented by graphite, alloy materials represented by CuSn alloys and NiTiSi alloys, Si-based materials represented by Si and SiO, and materials such as Li4Ti5O4. 12 Choose one or more from the group consisting of oxide-based materials, represented by [the group name is missing].

[0305] [Adhesive]

[0306] In the electrode of this embodiment, the adhesive contained in the electrode adhesive layer is not particularly limited, and known adhesives can be used. The adhesive may, for example, be any one or more selected from the group consisting of: rubber-like polymers represented by styrene-butadiene rubber and isoprene rubber; synthetic resins represented by polyethylene, polyimide, polyacrylic acid, and polyamide; styrene-butadiene-styrene block copolymers or their hydrogenates; thermoplastic elastomers such as styrene-ethylene-butadiene, styrene copolymers, styrene-isoprene, or styrene block copolymers or their hydrogenates; soft resin-like polymers represented by isotactic-1,2-polybutadiene, ethylene-vinyl acetate copolymers, and copolymers of ethylene with α-olefins having 3 to 12 carbon atoms; and fluorinated polymers represented by polytetrafluoroethylene, tetrafluoroethylene-ethylene copolymers, polyvinylidene fluoride, polypentafluoropropylene, and polyhexafluoropropylene.

[0307] [Conductive additives]

[0308] In the electrode of this embodiment, the conductive additive contained in the electrode mixture layer is not particularly limited, and known conductive additives can be used. For example, the conductive additive can be any one or more from the group consisting of graphite materials, acetylene black, carbon black, Ketjen black, carbon fibers, carbon nanotubes, and graphene.

[0309] [Electrode manufacturing method]

[0310] The manufacturing method of the electrode in this embodiment is not particularly limited. The electrode in this embodiment uses the stainless steel foil of this embodiment as the current collector and is manufactured by a known method. The manufacturing method of the electrode in this embodiment includes, for example, an electrode slurry preparation step and an electrode mixture layer formation step.

[0311] [Electrode paste preparation process]

[0312] In the electrode slurry preparation process, an electrode slurry for forming the electrode mixture layer is prepared. The electrode slurry can be prepared according to the desired electrode mixture layer. For example, it can be prepared by mixing active material, solvent, conductive additive, and binder. The type of solvent is not particularly limited; it can be an aqueous solvent or an organic solvent. In addition, when preparing an electrode slurry for all-solid-state batteries, for example, active material, solvent, solid electrolyte, and binder can be mixed. That is to say, regardless of the composition of the electrode slurry, the stainless steel foil of this embodiment can suppress pinholes.

[0313] The mixing method is adjusted appropriately based on the active material, binder, conductive additive, solid electrolyte, and solvent. In other words, the electrode slurry preparation process can be carried out using well-known methods.

[0314] [Electrode Mixture Layer Formation Process]

[0315] In the electrode paste layer forming process, an electrode paste layer is formed on the surface of the stainless steel foil of this embodiment. Specifically, a mixed electrode slurry is coated onto the surface of the stainless steel foil of this embodiment. The coating method is not particularly limited and can be a known method. For example, a coater with gaps can be used for coating. For example, a sprayer can be used for spraying coating.

[0316] Then, the electrode paste coated on the stainless steel foil in this embodiment is dried to form an electrode mixture layer. The drying method is not particularly limited and can be any known method. For example, it can be dried by heating at 75°C for 20 minutes. Alternatively, it can be dried without heating.

[0317] The electrodes of this embodiment can be manufactured through the above processes.

[0318] [Battery]

[0319] The battery of this embodiment includes the electrodes and electrolyte of this embodiment. As long as the battery of this embodiment includes the electrodes of this embodiment, other structures can be known structures and are not particularly limited. The battery of this embodiment may also include a separator, for example. The shape of the battery of this embodiment is not particularly limited; it can be cylindrical, square, coin-shaped, or sheet-shaped. Furthermore, the battery of this embodiment can be either a secondary battery or a primary battery. When the battery of this embodiment is a secondary battery, it can be, for example, a non-aqueous electrolyte secondary battery, an aqueous electrolyte secondary battery, or an all-solid-state secondary battery.

[0320] [Electrolytes]

[0321] The electrolyte conducts ions between the positive and negative electrodes. In the battery of this embodiment, the electrolyte is not particularly limited, and a known electrolyte can be used. The electrolyte can be either a liquid electrolyte or a solid electrolyte. The electrolyte is not particularly limited, and known electrolytes and solvents can be used. For example, the electrolyte can be any one or more selected from the group consisting of LiClO4, LiPF6, LiBF4, LiAsF6, LiCF6, LiCF3CO2, LiPF6SO3, LiN(SO2F)2, LiN(SO2CF3)2, Li(SO2CF2CF3)2, LiN(COCF3)2, and LiN(COCF2CF3)2. The solvent may be, for example, any one or more selected from the group consisting of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, vinylene carbonate, fluoroethylene carbonate, methyl ethyl carbonate, γ-butyrolactone, sulfolane, dimethyl sulfoxide, acetonitrile, dimethylformamide, dimethylacetamide, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dioxolane, and methyl acetate. That is, at least two of these solvents may be mixed. The solid electrolyte may also be, for example, a sulfide-based solid electrolyte. A sulfide-based solid electrolyte may also be, for example, a solvent consisting of Li3PS4, Li7P3S... 11 LPS-based systems, represented by Li6PS5Cl x Br (1-x) Argyrodite type, represented by (0≦x≦1), and Li 10 GeP2S 12 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 Choose one or more from the group consisting of thio-lithium silicon (Thio-LISICON), represented by [the group name is missing].

[0322] [Battery manufacturing method]

[0323] The manufacturing method of the battery in this embodiment is not particularly limited. For example, the battery in this embodiment is manufactured by a known method, in which a laminate is formed by stacking the electrode, electrolyte and counter electrode of this embodiment.

[0324] Example

[0325] The effects of the stainless steel foil of this embodiment will be further explained in detail through examples. The conditions in the following examples are merely examples used to confirm the feasibility and effects of implementing the stainless steel foil of this embodiment. Therefore, the stainless steel foil of this embodiment is not limited to this single example.

[0326] As raw materials for manufacturing stainless steel foil, steel sheets with the chemical composition shown in Table 1 are prepared. The thickness of the steel sheets is 20 μm. The steel sheets prepared as raw materials are all obtained by annealing at 800~1200℃ for 3~30 seconds.

[0327] [Table 1]

[0328]

[0329] The raw materials for each test number underwent a final cold rolling process. The arithmetic mean surface roughness Ra (μm) and rolling speed v (m / s) of the rolls used in each test number are shown in Table 2. This yielded stainless steel foil with a foil body having a thickness of 10 μm.

[0330] [Table 2]

[0331]

[0332] A degreasing process was performed on the stainless steel foil after the final cold rolling process. In tests 1-9 and 12-14, PR electrolytic degreasing was used as the degreasing treatment (shown as "PR electrolysis" in the "Degreasing Method" column of Table 2). In the PR electrolytic degreasing, a 70°C sodium hydroxide aqueous solution was used as the alkaline cleaning solution. The polarity switching time t in each test number is... s (seconds), concentration of alkaline cleaning solution c (mol / L), degreasing treatment time t t (seconds) and current density d (A / dm) 2 As shown in Table 2. The stainless steel foils for tests 1-9 and 12-14, after electrolytic degreasing by PR, were rinsed with pure water. Then, the stainless steel foils for each test number were allowed to dry completely.

[0333] In experiments 10 and 11, organic solvent degreasing was performed as the degreasing treatment (shown as "solvent degreasing" in the "Degreasing Method" column of Table 2). In organic solvent degreasing, stainless steel foil was immersed in an isohexane bath at room temperature for 30 seconds. After being removed from the isohexane bath, it was allowed to dry thoroughly to allow the isohexane to evaporate.

[0334] Through the above manufacturing processes, stainless steel foil of each test number is manufactured.

[0335] [Evaluation Test]

[0336] The following evaluation tests were performed on the stainless steel foils of each test number that were manufactured.

[0337] (Experiment 1) Determination of Organic Residue

[0338] (Experiment 2) Test for determination of three-dimensional arithmetic mean roughness Sa of surface

[0339] (Experiment 3) Coating performance evaluation test

[0340] The following is a description of each experiment.

[0341] [(Experiment 1) Determination of Organic Residue Content]

[0342] Based on the method described above in [Method for Determination of Organic Residue Content], the amount of organic residue (mg / m³) on the surface of the foil substrate in each test number was determined. 2 The amount of organic residue obtained (mg / m³) 2 (See Table 3.)

[0343] [Table 3]

[0344]

[0345] [Experiment 2: Measurement of the three-dimensional arithmetic mean roughness Sa of the surface]

[0346] Based on the method described above in [Method for Determination of Three-Dimensional Arithmetic Mean Roughness Sa], the three-dimensional arithmetic mean roughness Sa (μm) of the surface of the foil body in each test number was measured. The obtained three-dimensional arithmetic mean roughness Sa (μm) of the surface is shown in Table 3.

[0347] [(Experiment 3) Coating performance evaluation test]

[0348] Based on the method described in the above-described [Evaluation Method for Electrode Slurry Coating Performance], the coating performance of the electrode slurry in the stainless steel foil for each test number was evaluated. The area (mm²) of the obtained cavities was then calculated. 2 The area of ​​the shrinkage cavity is shown in Table 3. 2 In this case, it is determined that the shrinkage cavities in the electrode paste are sufficiently suppressed. The area of ​​the shrinkage cavity exceeds 0 mm.2 In such cases, it is determined that the shrinkage cavities in the electrode slurry have not been sufficiently suppressed.

[0349] [Evaluation Results]

[0350] Referring to Tables 1-3, the amount of organic residue on the surface of the stainless steel foils in experiments 1-9 was 2.0 mg / m³. 2 Therefore, when applying the electrode paste, pinholes in the electrode paste can be effectively suppressed.

[0351] On the other hand, in tests 10 and 11, organic solvent degreasing was performed instead of PR electrolytic degreasing during the degreasing process. Therefore, the amount of organic residue on the surface exceeded 2.0 mg / m³. 2 As a result, the pinholes in the electrode paste cannot be adequately suppressed during coating.

[0352] In experiment number 12, the polarity switching time t during the degreasing process was... s Too short. Therefore, the amount of organic residue on the surface exceeds 2.0 mg / m². 2 As a result, the pinholes in the electrode paste cannot be adequately suppressed during coating.

[0353] In experiment number 13, FA did not satisfy equation (A) in the final cold rolling process. As a result, the three-dimensional arithmetic mean roughness Sa of the foil body surface was greater than 0.15 μm. Furthermore, in the degreasing process, FB satisfied equation (B2) but not equation (B1). Therefore, the amount of organic residue on the surface exceeded 2.0 mg / m². 2 As a result, the pinholes in the electrode paste cannot be adequately suppressed during coating.

[0354] In test number 14, the FB level was too low during the degreasing process. Therefore, the amount of organic residue on the surface exceeded 2.0 mg / m³. 2 As a result, the pinholes in the electrode paste cannot be adequately suppressed during coating.

[0355] The embodiments of this disclosure have been described above. However, the above embodiments are merely illustrative examples for implementing this disclosure. Therefore, this disclosure is not limited to the above embodiments, and appropriate modifications can be made to the embodiments without departing from its spirit.

Claims

1. A stainless steel foil, It has a foil body made of stainless steel. The amount of organic residue on the surface of the foil body is 2.0 mg / m³. 2 the following.

2. The stainless steel foil as described in claim 1, The three-dimensional arithmetic mean roughness Sa of the surface of the foil body is less than 0.15 μm.

3. The stainless steel foil as described in claim 1, The stainless steel mentioned is a ferritic stainless steel. The chemical composition of the foil body is as follows: by mass%, it contains... C:0.001~0.030%、 Si: 0.01~1.00% Mn: 0.01~1.00% P:0.001~0.050%、 S:0.001~0.030%、 Ni: 0.01~0.50% Cr:12.00~20.00%、 Mo: 0.01~2.50%, N:0~0.100%、 Ti: 0~0.80%, Nb: 0~0.80%, and Zr:0~0.80%, The remainder consists of Fe and impurities.

4. The stainless steel foil as described in claim 2, The stainless steel mentioned is a ferritic stainless steel. The chemical composition of the foil body is as follows: by mass%, it contains... C:0.001~0.030%、 Si: 0.01~1.00% Mn: 0.01~1.00%, P:0.001~0.050%、 S:0.001~0.030%、 Ni: 0.01~0.50% Cr:12.00~20.00%、 Mo: 0.01~2.50%, N:0~0.100%、 Ti: 0~0.80%, Nb: 0~0.80%, and Zr:0~0.80%, The remainder consists of Fe and impurities.

5. The stainless steel foil as described in claim 1, The stainless steel mentioned is an austenitic stainless steel. The chemical composition of the foil body is as follows: by mass%, it contains... C:0.001~0.150%、 Si: 0.01~1.00% Mn: 0.01~2.00% P:0.001~0.045%、 S:0.001~0.030%、 Ni: 6.00~15.00% Cr:16.00~20.00%、 Mo: 0 ~ 2.50%, N:0~0.100%、 Ti: 0~0.50%, Nb: 0~0.12%, and Zr:0~0.10%, The remainder consists of Fe and impurities.

6. The stainless steel foil as described in claim 2, The stainless steel mentioned is an austenitic stainless steel. The chemical composition of the foil body is as follows: by mass%, it contains... C:0.001~0.150%、 Si: 0.01~1.00% Mn: 0.01~2.00% P:0.001~0.045%、 S:0.001~0.030%、 Ni: 6.00~15.00% Cr:16.00~20.00%、 Mo: 0 ~ 2.50%, N:0~0.100%、 Ti: 0~0.50%, Nb: 0~0.12%, and Zr:0~0.10%, The remainder consists of Fe and impurities.

7. An electrode comprising: The stainless steel foil as described in any one of claims 1 to 6; and An electrode mixture layer is formed on the surface of the stainless steel foil.

8. A battery, comprising: The electrode as claimed in claim 7; and Electrolytes.

Citation Information

Patent Citations

  • Collector and negative electrode material for lithium-ion secondary battery

    JP2010033782A